Edu-Smart Learning Management System with Iterative Model and Appreciative Inquiry for Distance Learning - Muhtarom, M; Agus Herlambang, Bambang; Saifuddin Zuhri, Muhammad (KnE Social Sciences, 2022)
During the COVID-19 pandemic, all learning activities began to be conducted online. Online learning aims to meet educational standards by utilizing information technology to distribute subject matter and enable collaboration between students and teachers. This concept is known as the learning management system (LMS). A solution to support online learning policies is an LMS with hybrid-based gamification features. This article discusses the design of a distance learning LMS with hybrid-based gamification features. Such an LMS is more attractive than other LMS systems because it is equipped with gamification features. Gamification aims to make learning more engaging by incorporating game thinking, game design, and game mechanics into the learning process. This application is a website that has been converted into native code for platforms like iOS and Android and the hybrid application can be accessed easily via a smartphone. Students can be motivated to learn by using gamification in the LMS. Keywords: Edu-smart, LMS, online learning